Analisis Usia Kehamilan, Pola Makan dan Dukungan Sosial terhadap Keluhan Emesis gravidarum pada Ibu Hamil - Nadea Feby Hapsari; Didik Sumanto; Nina Anggraeni Noviasari (Universitas Muhammadiyah Manado, 2026)
Emesis gravidarum is a common condition during the first trimester of pregnancy that may affect maternal physical well-being, nutritional status, and quality of life. This condition is multifactorial, involving biological, behavioral, and psychosocial factors. This study aimed to analyze the association between gestational age, dietary patterns, and social support with emesis gravidarum complaints. A quantitative analytic observational study with a cross-sectional design was conducted at Bangetayu Primary Health Center, Semarang, in October 2025. A total of 34 first-trimester pregnant women were recruited using total sampling. Data were collected using the PUQE-24 questionnaire to assess symptom severity, a Food Frequency Questionnaire (FFQ) to evaluate dietary patterns, and the Multidimensional Scale of Perceived Social Support (MSPSS) to measure social support. Spearman’s rank correlation test was applied with a significance level of p<0.05. The mean emesis gravidarum score was 7.38±1.923, with a mean gestational age of 9.32 weeks. Gestational age (p=0.004) and dietary patterns (p=0.019) were significantly associated with emesis gravidarum, whereas social support showed no significant association (p=0.231). Early gestation was linked to more severe symptoms, while better dietary patterns were associated with milder complaints. Early pregnancy monitoring and dietary education are recommended to reduce symptom severity.